Stories of human resilience in a changing climate - Ainio, Silvia Anna; Gionfra, Susanna (Routledge focus on environment and sustainability, 2026)
Stories of Human Resilience in a Changing Climate offers a captivating glimpse into the human face of climate change.Despite extreme climate-related events witnessed globally, many struggle to connect such global phenomena to their own lives in a tangible way. As a result, there is still a strong disconnect between the general awareness of climate change and the sense of urgency that inspires action. This book fills a critical void in the field by sharing 11 real-life experiences across five continents of the world, featuring ordinary people facing and adapting to the consequences of climate change in its different forms. Through gripping accounts of a nomad having to relocate from the desert to the nearest city, an indigenous person fighting back for land rights, and a winemaker finding creative solutions to increasing heatwaves, among other stories, the book humanises the challenges of climate change. By weaving scientific data with personal stories, the chapters deliver a compelling call to move beyond mere acknowledgment of the problem towards transformative action that respects the balance of ecosystems, fosters sustainable practices, and redefines our relationship with nature. Overall, the book highlights the urgent need for global awareness on what ultimately represents one of the most pressing challenges of our time, leaving readers inspired and empowered to create a more sustainable and resilient future.This accessible and impactful book will be of great interest to students and scholars of climate change and environmental sciences and communication, as well as community leaders and NGOs wanting to understand practical examples and insights of climate change phenomena. Views and opinions expressed are those of the authors only and do not necessarily reflect those of the European Union or the European Commission.